PERBEDAAN EFEK NECK EXERCISE DAN MCKENZIE EXERCISE TERHADAP NYERI PADA KASUS NECK PAIN AKIBAT AKTIVITAS DENGAN KOMPUTER - Raymod Oskar; Wahyuddin Wahyuddin; Heri Priatna; Ferian Nugraha (LPPM Universitas Abdurrab, 2024)
Objective: To determine the difference in the effect of neck exercise and McKenzie exercise on pain in cases of neck pain due to activity with a computer. Methods: This research is experiment quantitative with a comparative study of two different groups that are correlated with each other with pretest and posttest groups. The total sample was 22 active students of the regular class of physiotherapy faculty of Esa Unggul University class of 2019-2022 obtained by purposive sampling, then divided into two groups by the odd-even randomization-allocation method. Pretest and posttest data were measured by numeratic rating scale (NRS). Results: Normality test using Shapiro Wilk test obtained normal and abnormal distributed data. Homogeneity test using Levene's test obtained homogeneous data. The results of hypothesis testing I and II using t-test related, obtained the results of p <0.001 which means the p value is significant, which means that neck exercise and McKenzie exercise are effective in reducing pain in neck pain cases due to activities with computers. In the hypothesis III test using the Mann-Whitney test, the results obtained p=0.466 which means the p value is not significant, which means there is no significant difference between neck exercise and McKenzie exercise in reducing pain in cases of neck pain due to activity with a computer. Conclusion: Neck exercise is effective in reducing pain in cases of neck pain due to computer activities. McKenzie exercise is effective in reducing pain in cases of neck pain due to computer activities. There is no difference between neck exercise and McKenzie exercise in reducing pain in cases of neck pain due to computer activities.